A Novel Approach to Abstract the Design Information and Minimal Cover from the Restructured Java Program - K. S., Aparna; Kulkarni, R. N. (International Journal of Intelligent Systems and Applications in Engineering, 2024)
The software industry has undergone enormous development during the previous few decades. Java programming was used to create many of the software applications needed to run the current generic applications. To support the business operations, these applications have undergone changes based on the changing requirements of the customer or organization. Many changes performed during these need-based updates are made only to the applications and not in the relevant documents related to the software. Further altering these software systems could occasionally cause a software crash. It might be challenging to add new features to the old programs as there is a possibility of redundant code. To overcome the problems related with either redundancy of the code or documentation, a novel methodology is proposed and a tool is developed to abstract the various components from the input java programming system such as control flow graph, data flow information in the control flow order and the various attributes which are participating in the program. Further the data flow graph and control flow graph are used to find the functional dependencies and attribute closures. The abstracted attributes are used to find the minimal cover, which results in the computation of the functionality of the program.